On hashish - Benjamin, Walter, 1892-1940 (Belknap Press of Harvard University Press, 2006)
On Hashish provides a portrait of Benjamin, venturesome as ever at the end of the Weimar Republic, and of his unique form of thought." "Consciously placing himself in a tradition of literary drug-connoisseurs from Baudelaire to Hermann Hesse, Benjamin looked to hashish and other drugs for an initiation into what he called "profane illumination." At issue here is a way of seeing, a new connection to the ordinary world. Under the influence of hashish, as time and space becomes inseparable, what Benjamin, in his study of Surrealism, calls "image space" comes vividly to life in this philosophical immersion in the sensuous." "This English-language edition of On Hashish features a section of supplementary materials - drawn from Benjamin's essays, letters, and sketche